Sistem Penjadwalan Poliklinik Rawat Jalan Berbasis Manajemen Lean di RSUD Kota Padang - Adila Kasni Astiena; Rika Ampuh Hadiguna; Acim Heri Iswanto; Hardisman Hardisman; Dedy Irfan; Hariselmi Hariselmi (Warta Pengabdian Andalas, 2020)
Waiting is a waste that is common in outpatient services, especially at Regional General Hospitals, thus reducing the quality of service. The results of the 2018 and 2019 service studies at Rasidin Hospital, the waiting time for outpatient services was 239 and 122 minutes (standard ≤60 minutes). The queuing process started at night and the queue was overflowing in the morning which resulted in late medical record processing, less seating, and low patient satisfaction. The purpose of this service is to design a queue for outpatient services based on Lean Management. The service was carried out in February-July 2020. Lean Management reduces waste on everything involved in the service process, namely Supply, Input, Process, Output and Customer (SIPOC). The service target is the management, head of installation, registration officer, medical record, doctor and nurse and patient. Approaches in the form of surveys, brainstorming, trainning and FGDs for model building. The resulting model is written in a mobile-based application to facilitate queuing patients. The resulting model is an application for booking registration and consultation. Applications can be downloaded on the Googleplay Store. It takes 1 operator to run the application. This application is expected to decipher long queues, provide certainty of time and increase patient satisfaction. It takes commitment and discipline from all parties to carry out services that are on time as promised so that they run on target.